2019
DOI: 10.2337/dc18-2212
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal Nocturnal Glucose Control Is Associated With Large for Gestational Age in Treated Gestational Diabetes Mellitus

Abstract: Objective: Continuous glucose monitoring (CGM) provides far greater detail about fetal exposure to maternal glucose across the 24 hour day. Our aim was to examine the role of temporal glucose variation on the development of large for gestational age infants (LGA) in women with treated gestational diabetes (GDM). Research Design and Methods:A prospective observational study of 162 pregnant women with GDM in specialist multidisciplinary antenatal diabetes clinics. Participants undertook a 7-day masked CGM at 30-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 25 publications
6
79
0
Order By: Relevance
“…Importantly, a recent study demonstrated that mothers of large for gestational age (LGA) infants had significantly higher glucose overnight compared with mothers with normal for gestational age infants. Detecting and addressing nocturnal glucose control may help to further reduce rates of LGA in women with GD (20). The efficacy of CGM for GD is yet to be demonstrated in a well-designed RCT, however it seems logical that with proper training and education CGM could help pregnant women with GD prevent delivering LGA babies.…”
Section: Commentmentioning
confidence: 99%
“…Importantly, a recent study demonstrated that mothers of large for gestational age (LGA) infants had significantly higher glucose overnight compared with mothers with normal for gestational age infants. Detecting and addressing nocturnal glucose control may help to further reduce rates of LGA in women with GD (20). The efficacy of CGM for GD is yet to be demonstrated in a well-designed RCT, however it seems logical that with proper training and education CGM could help pregnant women with GD prevent delivering LGA babies.…”
Section: Commentmentioning
confidence: 99%
“… have shown that nocturnal glucose levels increased during the last two trimesters of pregnancy in women with pregestational diabetes who later deliver large‐for‐gestational‐age compared to non‐large‐for‐gestational‐age newborns. They recently confirmed this late pregnancy pattern in gestational diabetes . Nocturnal hyperglycaemia may therefore develop in the last trimester in women who previously had low basal rates of insulin infusion during the first hours after midnight, a rather common profile attributable to the dawn phenomenon.…”
mentioning
confidence: 76%
“…This insidious pattern will not be detected by conventional self‐monitored blood glucose, as underlined by Law et al . . By contrast, women on MDI, who usually use NPH as a basal insulin , may be protected from fetal growth acceleration and hyperglycaemia in the middle of the night, due to the action peak 4 h after the injection of NPH .…”
mentioning
confidence: 98%
“…We thank Foussard et al (1) for their insightful comments on our recent article (2). We demonstrated that women with gestational diabetes mellitus who subsequently have a large for gestational age (LGA) infant run significantly higher glucose overnight, detectable by continuous glucose monitoring (CGM), at 32 weeks' gestation than those women who do not go on to have an LGA infant (2).…”
mentioning
confidence: 94%